(De)Stabilizing exchange rate strategies in East Asian monetary and economic integration - Gunther Schnabl; Kristina Spantig (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2014)
The East Asian monetary integration process is at the crossroads. Given very benign liquidity conditions in the US, the prevailing common US dollar peg has contributed to growing macroeconomic and financial instability in the region. This has sparked demands to embark on an independent monetary integration process in East Asia. The paper shows that, however, neither the Japanese yen nor the Chinese yuan can challenge the US dollar has enhanced intra-regional exchange rate stability and growth, stressing the potential of the Chinese yuan to emerge as a regional anchor currency. Yet, it is shown that underdeveloped Chinese capital markets and financial repression originating in US lo winterest rate policies constitute an insurmountable impediment for the Chinese yuan to gain anchor currency status in East Asia. Empirical estimations provide evidence in favour of positive growth effects of the exchange rate stability against the US dollar in East Asia.
Keywords: F43; E42; F31; R11; 330; Japanese yen; Chinese yuan; intra-regional trade; informal dollar standard; exchange rate stabilization; business cycle stabilization; internationalization of the Chinese yuan